2002
DOI: 10.1074/jbc.m200347200
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Spectrum Caused by Transgenic Overexpression of Activated Akt in the Heart

Abstract: The serine-threonine kinase, Akt, inhibits cardiomyocyte apoptosis acutely both in vitro and in vivo. However, the effects of chronic Akt activation in the heart are unknown. To address this issue, we generated transgenic mice (TG؉) with cardiac-specific expression of a constitutively active mutant of Akt (myr-Akt) driven by the myosin heavy chain-␣ promoter. Three TG؉ founders (9 -19 weeks) died suddenly with massive cardiac dilatation. Two viable TG؉ lines (TG564 and TG20) derived from independent founders d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
313
2
16

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(346 citation statements)
references
References 49 publications
15
313
2
16
Order By: Relevance
“…Nuclear-targeted PKB overexpression has previously been shown to have several beneficial effects including enhanced contractility and protection from ischaemic injury [28], while sustained PKB activation can lead to hypertrophic cardiomyopathy primarily via phosphorylation of substrates localized to the cytoplasm [11,29], indicating that PKB not only plays important roles in the nuclei of cardiomyocytes, but that these roles can differ depending on its localization. Furthermore, we show that inhibition of PKB with triciribine causes ISO to behave as an inverse agonist, leading to the inhibition of RNA synthesis, as opposed to its previously noted stimulatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear-targeted PKB overexpression has previously been shown to have several beneficial effects including enhanced contractility and protection from ischaemic injury [28], while sustained PKB activation can lead to hypertrophic cardiomyopathy primarily via phosphorylation of substrates localized to the cytoplasm [11,29], indicating that PKB not only plays important roles in the nuclei of cardiomyocytes, but that these roles can differ depending on its localization. Furthermore, we show that inhibition of PKB with triciribine causes ISO to behave as an inverse agonist, leading to the inhibition of RNA synthesis, as opposed to its previously noted stimulatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…Akt itself is an important regulator of myocyte growth and survival, 25 and constitutive overexpression of Akt in transgenic mice has been found to lead to increased contractility 26 and pathological cardiac hypertrophy. 27,28 Clustered with Akt and gp130 was fibroblast growth factor-1, an angiogenic growth factor that has earlier been shown in human cardiac hypertrophy 29 and that may reflect that blood vessel recruitment is an important feature of normal tissue growth. 30 An increase in connective tissue growth factor (CTGF) expression was seen in late LVH, similar to findings in other models of cardiac hypertrophy, 31 and its well-characterized profibrotic effect, including its ability to induce cardiac fibroblast proliferation and also extracellular matrix expansion.…”
Section: Proliferation/cell Growthmentioning
confidence: 99%
“…Several studies have demonstrated deleterious effects of chronically upregulated Akt signalling in the heart [13,14,27,28]. Accordingly, it appears consistent that a pharmacologically controlled inhibition of Akt activity by celecoxib has cardioprotective effects.…”
Section: Discussionmentioning
confidence: 87%
“…The molecular mechanisms determining the difference between physiological and pathological hypertrophy are still poorly understood. Whereas some authors hypothesize distinct signalling systems for the different types of hypertrophy [1,[10][11][12], there is now growing evidence that identical pathways can induce both, adaptive and maladaptive hypertrophy, depending on the intensity and duration of their activation [13,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%